2006
DOI: 10.1002/mds.21227
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of brain iron and neuronal integrity in patients with Parkinson's disease using novel MRI contrasts

Abstract: Postmortem demonstration of increased iron in the substantia nigra (SN) is a well-appreciated finding in Parkinson's disease (PD). Iron facilitates generation of free radicals, which are thought to play a role in dopamine neuronal loss. To date, however, magnetic resonance imaging (MRI) has failed to show significant in vivo differences in SN iron levels in subjects with PD versus control subjects. This finding may be due to the limitations in tissue contrasts achievable with conventional T(1)- and T(2)-weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 37 publications
8
114
1
1
Order By: Relevance
“…Our results are in concordance with several previous studies reporting increased iron depositions in the SN of patients with multiple system atrophy and IPD. 15,[42][43][44][45][46][47] A few studies [48][49][50] used SWI images to detect putative iron content in the brain as a tool to differentiate MSA-P from IPD. Gupta et al 49 investigated SWI for patterns of mineralization to differentiate progressive supranuclear palsy, IPD, and multiple system atrophy; minimum-intensity-projection images of SWI were used to obtain signal intensities of each nucleus, which did not demonstrate a significant difference between IPD and multiple system atrophy, though higher putaminal hypointensity scores were found in patients with multiple system atrophy compared with those with IPD.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in concordance with several previous studies reporting increased iron depositions in the SN of patients with multiple system atrophy and IPD. 15,[42][43][44][45][46][47] A few studies [48][49][50] used SWI images to detect putative iron content in the brain as a tool to differentiate MSA-P from IPD. Gupta et al 49 investigated SWI for patterns of mineralization to differentiate progressive supranuclear palsy, IPD, and multiple system atrophy; minimum-intensity-projection images of SWI were used to obtain signal intensities of each nucleus, which did not demonstrate a significant difference between IPD and multiple system atrophy, though higher putaminal hypointensity scores were found in patients with multiple system atrophy compared with those with IPD.…”
Section: Discussionmentioning
confidence: 99%
“…The thalamus and white matter contain little to no iron (Hallgren and Sourander, 1958) and therefore exhibit no T 2 * effect from iron (Bartzokis et al, 1993). Other structures, including the putamen and caudate, however, are vulnerable to further accumulation of iron with advancing age (Bartzokis et al, 1994(Bartzokis et al, , 2007b, and the iron accumulation is abnormally high in diseases of the basal ganglia, such as Parkinson's disease (Bartzokis et al, 1999;Michaeli et al, 2007;Pujol et al, 1992), striatonigral degeneration , and Huntington's disease (Bartzokis et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…However, R2' and R2* did not correlate with clinical impairment. In another study, using the T2 rho MRI method, Michaeli et al 50 showed increased substantia nigra iron levels in patients with PD versus normal controls. Kosta et al 100 compared T2 intensity in the substantia nigra pars compacta and subthalamic nucleus in 40 patients with PD and 40 normal controls.…”
Section: Parkinson's Diseasementioning
confidence: 97%
“…Wheaton et al 49 demonstrated an increase in iron-related contrast when comparing images created with T2 rho to conventional T2 in the normal human brain. Using a 4T magnet with a rotating frame and applying adiabatic pulses, Michaeli et al 50 demonstrated a statistically significant shortening of relaxation times in substantia nigra tissue in patients with PD compared to normal controls with T2 rho but not with routine T2. This correlates with postmortem observations of excessive iron deposition associated with the disease and suggests that this novel technique generates better iron-related contrast than conventional T2 methodology.…”
Section: Relaxometrymentioning
confidence: 99%